1967
DOI: 10.1071/ch9671097
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose crystal growth. II. Rate of crystal growth in the presence of impurities

Abstract: The effects are described of supersaturation, temperature, and relative motion of solution and crystal on the rate of sucrose crystal growth from aqueous solutions containing a wide range of impurities. The results are consistent with the conclusion, drawn from data in pure sucrose solution, that two main steps, neither of which are clearly rate-controlling under the experimental conditions, are important in crystal growth kinetics. Impurities can be classified broadly as those which have their main effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…The effects of other components, e.g. soluble proteins and salts, on vitrification were not tested; however, Smythe (9) found that the crystallization of sucrose was not impeded significantly by organic acids and salts; the most effective inhibitors of sucrose crystallization were oligosaccharides. This implies that not all cell components can interrupt the crystalline matrix of sucrose, and that raffinose may be necessary to ensure the formation of a glass rather than a crystal during drying.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of other components, e.g. soluble proteins and salts, on vitrification were not tested; however, Smythe (9) found that the crystallization of sucrose was not impeded significantly by organic acids and salts; the most effective inhibitors of sucrose crystallization were oligosaccharides. This implies that not all cell components can interrupt the crystalline matrix of sucrose, and that raffinose may be necessary to ensure the formation of a glass rather than a crystal during drying.…”
Section: Methodsmentioning
confidence: 99%
“…In addition this attachment does not induce any raffinose XRD peaks (Vaccari et al, 1986;Mantovani et al, 1977;1983;Mathlouthi and Reiser, 1995). Smythe (1967) and Iglesias et al(2000) also found that raffinose slows the crystallization of sucrose in aqueous solutions and that the optimal equilibrium state of crystalline raffinose is as a pentahydrate form, therefore, a relatively large amount of water is needed to completely crystallize it. Pure raffinose also has a higher glass transition temperature as compared to pure sucrose and may work in the same way trehalose inhibited crystallization of sucrose as found by Roe and Labuza (2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sucrose has been shown to protect soluble enzymes from salt-induced damage in vitro (32). The presence of a larger oligosaccharide along with sucrose may enhance protection still further by favoring vitrification rather than crystallization (6,9,17,33,35).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, sucrose has been shown to protect soluble enzymes from salt-induced damage in vitro (32). The presence of a larger oligosaccharide along with sucrose may enhance protection still further by favoring vitrification rather than crystallization (6,9,17,33,35).Although oligosaccharides such as stachyose have been recognized as protective agents in leaves against cold-induced damage, they are often referred to as a carbon reserve for germination rather than as a desiccation protectant in the axes of nonendospermic legume seeds (12). Raffinose and stachyose are synthesized by the following reactions (12) catalyzed by galactinol synthase (UDP-galactose:inositol galactosyltransferase) (Eq.…”
mentioning
confidence: 99%